73 Prevalence and prognostic significance of ischaemic late gadolinium enhancement pattern in non-ischaemic dilated cardiomyopathy. (8th December 2021) - De Angelis, Giulia; De Luca, Antonio; Merlo, Marco; Nucifora, Gaetano; Rossi, Maddalena; Stolfo, Davide; De Bellis, Annamaria; Barbati, Giulia; Santangeli, Pasquale; Mase, Marco; Pagnan, Lorenzo; Muser, Daniele; et al.
Abstract: Aims: Typical late gadolinium enhancement (LGE) patterns in dilated cardiomyopathy (DCM) include intramyocardial and subepicardial distribution. However, the ischaemic pattern of LGE (subendocardial and transmural) has also been reported in DCM without coronary artery disease (CAD), but its correlates and prognostic significance are still not known. On these bases, this study sought to describe the prevalence and prognostic significance of the ischaemic LGE pattern in DCM. Methods and results: 611 DCM patients with available cardiac magnetic resonance were retrospectively analysed. A composite of all-cause-death, major ventricular arrhythmias (MVAs), heart transplantation (HTx) or ventricular assist device (VAD) implantation was the primary outcome of the study. Secondary outcomes were a composite of sudden cardiac death or MVAs and a composite of death for refractory heart failure, HTx or VAD implantation. Ischaemic LGE was found in 7% of DCM patients without significant CAD or history of myocardial infarction, most commonly inferior/inferolateral/anterolateral. Compared to patients with non-ischaemic LGE, those with ischaemic LGE had higher prevalence of hypertension and atrial fibrillation or flutter. Ischaemic LGE was associated with worse long-term outcomes compared to non-ischaemic LGE (36% vs. 23% risk of primary outcome events at 5 years, respectively, P  = 0.006), and remained an independent predictor of primary outcome after adjustment for clinically and statistically significant variables [adjusted hazard ratio 2.059 (1.055–4.015), P  = 0.034 with respect to non-ischaemic LGE]. Conclusions: The ischaemic pattern of LGE is not uncommon among DCM patients without CAD and is independently associated with worse long-term outcomes.